FACTORS AFFECTING STOCK RETURN OF COMPANIES ENTERED IN IDX HIGH DIVIDEND 20 - Fachrizal Yusuf Apriansyah; Ninik Lukiana; Hesti Budiwati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
This study aims to examine and analyze the effect of Dividend Policy using the Dividend Payout Ratio proxy, Liquidity using the Current Ratio proxy, and Profitability using the Return On Equity proxy. This research was conducted on companies that are included in IDX High Dividend 20 for the 2015-2017 period. Sampling used in this research is using purposive sampling technique that gets 20 companies as research samples and uses multiple linear regression analysis for data processing. The type of data used is secondary data in the form of financial reports, and the data sources are internal data and external data. The results in this study state that partially dividend policy has a significant effect on stock returns, Likewise, liquidity does not have a significant effect on stock returns, and profitability also does not have a positive and significant effect on stock returns. The limitation of this study is that it only uses dividend policy, liquidity, and profitability variables to determine the impact on stock returns. While other variables that can affect stock returns are not examined and are expected to be continued by other researchers.